The Role of HR Analytics in Strategic Decision Making: Leveraging Data for Talent Management - Tuli, Ferdouse Ara; Sachani, Dipakkumar Kanubhai; Vennapusa, Sai Charan Reddy (Asian Business Review, 2024)
The study examines how HR analytics may revolutionize talent management and strategic decision-making. This study delves into the acceptance of advanced analytics techniques in HR, the obstacles encountered during implementation, and the emerging trends that will shape the industry through an extensive literature review and analysis of case studies. Important conclusions draw attention to better decision-making procedures, improved talent management techniques, and policy ramifications, such as the necessity of extensive data privacy laws and funding for the professional development of HR personnel. The study highlights HR analytics’ importance in achieving competitive advantage and organizational success in the digital age.